Deconstruction of the Innovation Path of Digital Transformation Based on Network Big Data Security in the Context of Smart City. (11th October 2022) - Chen, Tang; Chen, Pengyu; Chen, Guang
Abstract : Digital transformation means that traditional enterprises have combined commerce, administration, and manufacturing with cloud services, the use of big data, and the web to advance the modern transformation of their research and development, creation, manufacturing and assembly, administration of operations, commercial support, and more tasks. Digital transformation showed that only companies can radically and completely (or substantially and completely) redefine their business—not just IT but all aspects of organizational activities, processes, business models, and employee capabilities. Only then can success be achieved. This paper aimed to study the innovative path of digital transformation and propose a network-based big data security method. Combined with the experimental analysis, it was concluded that using network big data security to monitor computer and network security (CNS), the attack detection accuracy rate is up to 99.8%. It can be seen that this method can accurately capture the shortcomings and leaks in the process of digital transformation, help achieve targeted path innovation, and improve the technological improvement and asset income growth of enterprises in the context of smart cities.